Faktor-Faktor Yang Memengaruhi Pola Konsumsi Pangan Rumah Tangga : (Studi Kasus Desa Sumberejo Kecamatan Wonosalam Kabupaten Jombang) - Arief, Sjamsul; Kusmaningtyas, Amiartuti (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2021)
This study aims to examine, analyze and prove Engel's Law which says that "the smaller a person's income, the greater the portion of that income will be used to meet food consumption. Conversely, the greater a person's income, the smaller the portion of that income will be used to meet food consumption. Furthermore, this study will also analyze the factors that influence household food consumption patterns in accordance with prevailing theories and laws of demand, such as the level of household income, the price of goods, the number of household members and possibly the level of education. This research is a survey research using a questionnaire distributed to respondents (heads of families). The object of this research is the pattern of household food consumption in Sumberejo Village, Wonosalam District, Jombang Regency. The data used are primary data collected through direct interviews using a questionnaire addressed to each household (respondent) selected as the sample in this study. The data analysis used descriptive analysis to explain the real condition of the respondents and correlation regression to measure the influence of the factors on the consumption pattern of the family household. Statistical testing is done to test the validity and reliability of the data so that conclusions can be drawn from the results of the regression analysis. From the analysis and discussion of the factors that influence household food consumption patterns in Sumberejo Village, Wonosalam District, Jombang Regency, it can be concluded as follows: 1) The share of household expenditure on food consumption is still relatively high, and this shows that the level of household welfare the ladder in the village of Sumberejo, Wonosalam district, Jombang district is still low. There is a difference in the share of non-farmer household expenditures which shows a smaller value compared to farmer households, which means that non-farmer households are more prosperous than farmer households, 2) Partially food prices, household income levels and number of household members tang has a significant (significant) effect on household food consumption patterns in the village of Sumberejo, Wonosalam district, Jombang district. On the other hand, the education level factor of the head of the household has an insignificant (insignificant) effect on the pattern of household food consumption in the village of Sumberejo, Wonosalam sub-district, Jombang district, and 3) Together (simultaneously), food prices, household income levels, The number of household members and the education level of the head of the household have a significant (significant) effect on the pattern of household food consumption in the village of Sumberejo, Wonosalam sub-district, Jombang Regency.